A Cross-Cultural Psycholinguistic Study on Arabic Vocabulary Retention: Evidence from Indonesia and Malaysia - Baharun, Segaf; Hanifansyah, Nur; Atiyah, Nur Adilah (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2025)
This study examines Arabic vocabulary retention from a cross-cultural psycholinguistic perspective involving learners in Indonesia and Malaysia. Recognizing that rote memorization rarely ensures long-term retention, the research integrates association, mnemonics, visualization, and a novel strategy Familiarity-Enhanced Recall to enhance recall and reduce anxiety. Employing a mixed-method design, 90 participants (30 from Pondok Pesantren Darullughah Wadda’wah, Indonesia, and 60 from Maktab Mahmud Yan, Malaysia) completed pre-tests, post-tests, and interviews. Results showed significant improvement, with Familiarity-Enhanced Recall linking new words to familiar routines, cultural practices, or personal hobbies emerging as the most effective approach. Learners expressed greater confidence, motivation, and emotional engagement, as vocabulary became personally meaningful and easier to recall. The findings underscore that psycholinguistic strategies, when contextualized within learners’ cultural experiences, foster more sustainable and engaging vocabulary acquisition, offering valuable insights for Arabic language pedagogy in diverse educational settings.